(untitled) (European Journal of Health Research, 2016)
A line of research that has attracted a great interest is the study of personal beliefs about the ability to enjoy life and that may be affected in people with alexithymia. The objectives were to analyze the relationship between alexithymia and capacity for the enjoyment of life by comparing a group of students enrolled in the older classroom of Murcia University with a group of users within an institutionalized elderly. A cross-sectional design was used. Study participants were 80 subjects of whom 50 people were in the senior classroom (M: 68.86 years; DT: 11,99). Abbreviated Toronto Alexithymia Scale (TAS-20) and the Beliefs About Enjoy Life Questionnaire were used in the study. The relevant permits were requested to the management center/director of the institutionalized elderly and the senior classroom. The results showed that institutionalized people lowest in Enjoy the Moment. Significant correlations between reminiscent of the good times and the difficulty in identifying feelings were found, as well as with the pattern of externally oriented thinking. It is important to develop programs which promote the enjoyment of life to manage emotions in people with alexithymia.